PENGEMASAN PAKET WISATA BERBASIS NEWA (NATURE, ECO, WELLNESS AND ADVENTURE) DI DESA WISATA TUA, TABANAN - ., Kardianto; Sasrawan Mananda, IGPB.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata), 2024)
Post-pandemic tourism trends relate to nature-based sustainable tourism activities, such as nature based tourism, ecotourism, adventure tourism and wellness tourism commonly referred to as NEWA (nature, ecotourism, wellness tourism and adventure). One of the villages in Tabanan that has this potential is the Tua Tourism Village, however the tourist activities available are still limited so that the length of stay of tourists is still short. Therefore, it is necessary to conduct a more in-depth study related to the existing tourism potential and then package it into a NEWA-based tour package. This research uses a qualitative approach with observation, in-depth interviews, documentation and literature studies. The concept of 4A tourism components (attraction, amenities, accessibilities and ancillary) used to identify tourism potential based on NEWA. The data collected was processed using qualitative descriptive analysis techniques. The results showed that the tourism potential in Tua Tourism Village consists of natural potential: Pohon Kayu Putih and Campuhan Yeh Kakul Waterfall, ecotourism potential: Rice and Pacar rice fields, Chocolate Village and Trigona honey farm, wellness potential: Yoga, Meditation and Herbal Medicine and adventure potential: Cycling and trekking activities. This potential can be packaged into ready-made packages, namely the Cycling Expedition tour: Adventure and Natural Healing" and Discovering Village Vistas: Exploring Tua's Rural Trail with a duration of two days one night.